Influenza A Viruses: Understanding Human Host Determinants. Issue 2 (February 2021) - Ciminski, Kevin; Chase, Geoffrey P.; Beer, Martin; Schwemmle, Martin
Abstract : Previous influenza A virus (IAV) pandemics have invariably been caused by the introduction of an emergent IAV strain from an animal host into a human population with no or only little pre-existing immunity to the novel strain. Although zoonotic spillover of IAVs into humans can be associated with severe disease and a high fatality rate, these strains are typically poorly adapted to humans and are unable to establish sustained transmission between humans. Given the presumably very high degree of exposure to animal populations with endemic IAV, the number of pandemics remains surprisingly low. In this review, we provide an updated perspective on the molecular mechanisms underlying the adaptation of zoonotic IAV to human hosts, and discuss the implications for future pandemics. Highlights: The ability of influenza A virus (IAV) to alter its genotype through antigenic drift and antigenic shift leads to recurring host switch events in which a zoonotic strain becomes established in humans. Such novel IAV strains are the cause of IAV pandemics in humans, who have no to little protective immunity to viral surface proteins of avian origin. The major barriers to human infection and transmission by zoonotic IAV are the cellular entry receptor sialic acid (SA), the human antiviral restriction factor myxovirus resistance protein 1 (MxA), and intracellular proteins required for efficient viral replication. While the IAV surface proteins hemagglutinin (HA) and neuraminidase (NA) appear capable of switching from avian to human hosts with few mutations, MxA antagonism requires the concurrent accumulation of multiple mutations in nucleoprotein (NP), which attenuate the virus in avian hosts, thus pointing to a requirement for an intermediate 'mixing vessel' host species, such as swine.